2012
DOI: 10.7883/yoken.65.315
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based Detection of Leishmania DNA in Skin Samples of Post Kala-Azar Dermal Leishmaniasis Patients from an Endemic Area of Bangladesh

Abstract: SUMMARY: Post kala-azar dermal leishmaniasis (PKDL) is a sequel of visceral leishmaniasis (VL) and PKDL patients are an important reservoir for anthroponotic transmission of VL. Therefore, diagnosis and treatment of PKDL is important for the kala-azar elimination program in South Asia, including Bangladesh. While definitive diagnosis of PKDL is still based on microscopy, despite the low sensitivity of this method of diagnosis, PCR for identification of kinetoplast DNA (kDNA) from Leishmania parasites is expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Our study revealed nearly similar results by nested PCR, whereas detection by imprint smear microscopy was much higher than reported in the other studies. We used the rRNA gene of the ITS region, whereas in the Bangladesh, India, and Sudan studies, a minicircle of kinetoplast DNA (kDNA) and the 18S rRNA gene were employed for the PCR (11,12,15).…”
Section: Downloaded Frommentioning
confidence: 99%
See 4 more Smart Citations
“…Our study revealed nearly similar results by nested PCR, whereas detection by imprint smear microscopy was much higher than reported in the other studies. We used the rRNA gene of the ITS region, whereas in the Bangladesh, India, and Sudan studies, a minicircle of kinetoplast DNA (kDNA) and the 18S rRNA gene were employed for the PCR (11,12,15).…”
Section: Downloaded Frommentioning
confidence: 99%
“…In a recent study conducted in Bangladesh, positivity by nested PCR in macular lesions was 93.2%, whereas microscopy had indicated only 2.7% positive samples, with overall positive results of 94.5% and 29.1%, respectively (11). Similar studies from India and Sudan reported positive PCR results in 93% and 82.7% of samples, whereas by microscopy the positive rates were 30.4% and 54%, respectively (12,15).…”
mentioning
confidence: 95%
See 3 more Smart Citations